Parametric analysis of a high temperature packed bed thermal storage design for a solar gas turbine. (August 2015) - Klein, P.; Roos, T.H.; Sheer, T.J.
Highlights: Alumina is a suitable storage material, with a high volumetric heat storage density. Numerical model is validated against high temperature experimental data. Validated model is used to conduct a parametric design study for a 1.55 MW hth storage. Hybridisation improves storage efficiency and utilisation factors. Optimal configuration yields efficiency of 88% and utilisation factor of 85%. Abstract: The development of a high temperature Thermal Energy Storage (TES) system will allow for high solar shares in Solar Gas Turbine (SGT) plants. In this research a pressurised storage solution is proposed that utilises a packed bed of alumina spheres as the storage medium and air from the gas turbine cycle as the heat transfer fluid. A detailed model of the storage system is developed that accounts for transient heat transfer between discrete fluid and solid phases. The model includes all relevant convective, conductive and radiative heat transfer mechanisms and is validated against high temperature experimental data from a laboratory scale test facility. The validated model is further utilised to conduct a parametric design study of a nominal six hour TES ( 1.55 MW h th ) for a gas micro-turbine. The concepts of utilisation factor and storage efficiency are introduced to determine the optimal storage design. The results of the study indicate that a storage efficiency of 88% and utilisation factor of 85% can be achieved when combining thermal storage and hybridisation with fossil fuels.